Detection of circulating trophoblast particles in maternal blood using density gradient centrifugation in preeclampsia and in normotensive pregnancies. (2nd July 2016) - Kuessel, Lorenz; Kasimir-Bauer, Sabine; Zeillinger, Robert; Pateisky, Petra; Ott, Johannes; Zeisler, Harald; Birdir, Cahit
ABSTRACT: Objective : Preeclampsia (PE) is a frequent pregnancy-related disease and a major cause of maternal and fetal morbidity and mortality. Despite that, exact mechanisms of its pathophysiology remain largely unknown. In pregnancies complicated by PE, changes in the regulation of apoptosis seem to result in increased apoptotic shedding of trophoblast particles (TPs) into maternal circulation. Since the number of TP in peripheral blood is low, their detection necessitates pre-analytical enrichment. Methods : In this prospective multicenter pilot study we aimed to analyze TP in peripheral blood of 29 women with PE and of 13 unaffected controls using the OncoQuick®plus system for cell enrichment. Using immunocytochemistry, slides were evaluated microscopically for TP. Statistical analyses were performed using Welch's t -test or Fisher's exact test. Results : TP were detected in 10 (34.5%) women with PE and in two (15.4%) of unaffected controls. More than one TP were only found in PE. Comparing the mean counts of TP between groups, we detected significantly more TP in PE ( p = 0.046). Conclusions : The OncoQuick®plus system can be applied to detect TP in both women with PE and in normotensive pregnancies. Longitudinal studies investigating the role of TP as a screening method for patients at risk for PE are warranted.